Rationalizing Pricing Decisions Through Target Costing: A Qualitative Analysis Of A Real Estate Development Company’s Off-Plan Sales - Mohammed A, Alrubayan Lulwah (2025)
The main objective of this study is to examine the impact of target costing (TC) in rationalizing off-plan residential unit pricing decisions and to explore how TC was implemented in a real estate development company in Saudi Arabia.